Non-alcoholic Fatty Liver Disease and Alcohol-Related Liver Disease: Two Intertwined Entities - Idalsoaga, Francisco; Kulkarni, Anand V.; Mousa, Omar Y.; Arrese, Marco; Arab, Juan Pablo (Frontiers in Medicine, 2020)
Nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease worldwide, with a prevalence of 25-30%. Since its first description in 1980, NAFLD has been conceived as a different entity from alcohol-related fatty liver disease (ALD), despite that, both diseases have an overlap in the pathophysiology, share genetic-epigenetic factors and frequently coexist. Both entities are characterized by a broad spectrum of histological features ranging from isolated steatosis to steatohepatitis and cirrhosis. Distinction between the two entities is based on the amount of consumed alcohol, which has been arbitrarily established. In this context, a proposal of positive criteria for NAFLD diagnosis not considering exclusion of alcohol consumption as a prerequisite criterion for diagnosis had emerged, recognizing the possibility of a dual etiology of fatty liver. The effects of moderate alcohol use on severity of liver disease in patients with NAFLD remain ill-defined with some studies suggesting protective effects in moderate doses to current evidence showing that there is no safe threshold for alcohol consumption in the context of NAFLD. In fact, given the synergistic effect between alcohol consumption and obesity and metabolic dysfunction, it is likely that alcohol use acts as a significant risk factor for the progression of liver disease in subjects with NAFLD and metabolic syndrome also affecting the incidence of hepatocellular carcinoma. In this review, we summarize the overlapping pathophysiology of NAFLD and ALD, the currently available data on alcohol consumption in patients with NAFLD and the effects of metabolic dysfunction and overweight in ALD.